Evaluation and use of an anti‐cynomolgus monkey CD79b surrogate antibody–drug conjugate to enable clinical development of polatuzumab vedotin. (24th August 2019) - Li, Dongwei; Lee, Donna; Dere, Randall C.; Zheng, Bing; Yu, Shang‐Fan; Fuh, Franklin K.; Kozak, Katherine R.; Chung, Shan; Bumbaca Yadav, Daniela; Nazzal, Denise; Danilenko, Dimitry; Go, Mary Ann T.; et al.
Abstract : Background and Purpose: Polatuzumab vedotin is an antibody–drug conjugate (ADC) being developed for non‐Hodgkin's lymphoma. It contains a humanized anti‐CD79b IgG1 monoclonal antibody linked to monomethyl auristatin E (MMAE), an anti‐mitotic agent. Polatuzumab vedotin binds to human CD79b only. Therefore, a surrogate ADC that binds to cynomolgus monkey CD79b was used to determine CD79b‐mediated pharmacological effects in the monkey and to enable first‐in‐human clinical trials. Experimental Approach: Polatuzumab vedotin, the surrogate ADC, and the corresponding antibodies were evaluated in different assays in vitro and in animals. In vitro assessments included binding to peripheral blood mononuclear cells from different species, binding to a human and monkey CD79b‐expressing cell line, binding to human Fcγ receptors, and stability in plasma across species. In vivo, ADCs were assessed for anti‐tumour activity in mice, pharmacokinetics/pharmacodynamics in monkeys, and toxicity in rats and monkeys. Key Results: Polatuzumab vedotin and surrogate ADC bind with similar affinity to human and cynomolgus monkey B cells, respectively. Comparable in vitro plasma stability, in vivo anti‐tumour activity, and mouse pharmacokinetics were also observed between the surrogate ADC and polatuzumab vedotin. In monkeys, only the surrogate ADC showed B‐cell depletion and B‐cell‐mediated drug disposition, but both ADCs showed similar MMAE‐driven myelotoxicity, as expected. Conclusions and Implications: The suitability of the surrogate ADC for evaluation of CD79b‐dependent pharmacology was demonstrated, and anti‐tumour activity, pharmacokinetics/pharmacodynamics, and toxicity data with both ADCs supported the entry of polatuzumab vedotin into clinical trials.